2019
DOI: 10.19045/bspab.2019.80110
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization induced drought tolerance in sunflower: a review

Abstract: Drought is one of the most common abiotic stresses that badly effect plant growth, causes yield losses. Sunflower requires less water and thus has the capability to survive under drought stress condition. A drought stress condition affect various plant processes reducing plant growth, lessen the developmental stages of cell and tissues, and causes many changes in physiological, morphological and biochemical processes. Nitrogen is the major nutrient among all the nutrients because of its multifarious effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, they are a part of organic molecules with osmoregulation and antioxidant capacity. Thus, it is not surprising that additional inputs of N and P have a beneficial effect on plants under drought stress (Tariq et al, 2018;Mahpara et al, 2019). With respect to K + , in cotton (Pervez et al, 2004) and citrus crops (Gimeno et al, 2014), it has been observed that an adequate level of K + in the irrigation water increases their tolerance to drought.…”
Section: Improving Crop Yield Under Drought In the Fieldmentioning
confidence: 99%
“…However, they are a part of organic molecules with osmoregulation and antioxidant capacity. Thus, it is not surprising that additional inputs of N and P have a beneficial effect on plants under drought stress (Tariq et al, 2018;Mahpara et al, 2019). With respect to K + , in cotton (Pervez et al, 2004) and citrus crops (Gimeno et al, 2014), it has been observed that an adequate level of K + in the irrigation water increases their tolerance to drought.…”
Section: Improving Crop Yield Under Drought In the Fieldmentioning
confidence: 99%
“…Previous studies have suggested that shoot biomass is more affected under drought-cum-nitrogen stress, while root biomass is not much exaggerated primarily [79]. On the other hand, plants become drought hardy under sufficient soil nitrogen availability [75,80,81]. Increasing nitrogen significantly improved crop performance under drought stress.…”
Section: Nitrogenmentioning
confidence: 95%
“…Under dry climatic conditions, water use efficiency and growth of crops is restricted due to less accessibility of water. Efficient nitrogen application can serve the purpose under drought stress [75,76]. Plants facing drought stress are more susceptible to heat tremors as well.…”
Section: Nitrogenmentioning
confidence: 99%
“…Different morphological, physiological and biochemical properties were disturbed because of drought stress conditions [6,8]. Photosynthetic imbalance, disturbance of electrolyte leakage, respiration impairing, poor accumulation of carbohydrates, imbalance ion exchange, cell division restriction and nutritional metabolism [9,10]. Consequently, it is more urgent and time need to situate more efforts aimed at improvement of cotton with excellent traits by using several drought resistant cultivars, better management practices, sufficient nutrition management and numerous cultural practices.…”
Section: Introductionmentioning
confidence: 99%